Pode o museu ser um jardim? = Can the museum be a garden? - Ribas, João (Fundação de Serralves, 2015)
The museum, like the garden, is a place for wandering and contemplation. With its flora and artifice, the garden is a space for cultivation and pleasure, but it is also an idea, a metaphor, the intersection between nature, culture, and science. Walking in a museum, a narrative unfolds before us, its many paths and streams connecting knowledge with the senses. Whether wild or mannerist, ordered or picturesque, the garden, like the museum, is experiential and affective, a space in which we are invited to wander through a landscape in perpetual growth, with forms, objects and colours arranged in space. As the garden represents the rational ordering of the natural world, so an exhibition is a garden of images, ideas, and emotions. Both places intertwine walking with the imagination. ‘Can the museum be a garden?’ engages these conceptual and historical relations between the garden and the museum. While some artworks drawn from the collection of the Serralves Museum directly address ideas of landscape and nature — from the use of natural materials to the movement of plants — others treat the garden as an expanded metaphor for seeing the world. In addition to these works from the collection, additional works by Hans Haacke and Louise Lawler have been ‘planted’ within the museum for the exhibition, as new species growing alongside the well-cared-for garden that a museum collection represents. As an exhibition, ‘Can the Museum be a Garden?’ will itself change with the seasons. In relating the exterior space of the garden with the interior space of the museum, the exhibition also draws on the unique setting of the landscape designed by Jacques Gréber, and the architecture of the Serralves Museum itself, conceived by Álvaro Siza. ‘Can the Museum be a Garden?’ engages the museum as a place for wandering and wondering, charting new paths through its spaces, and the act of walking as an aesthetic and contemplative practice.
Keywords: Fundação de Serralves (Portugal) / Art collections / Exhibitions; Geschichte 1960-2014; Art, Modern / 21st century / Exhibitions; Nature in art / Exhibitions; Landscapes in art / Exhibitions; Landschaft -- Motiv; Kunst; Garten -- Motiv; Ausstellungskatalog; Ausstellungskatalog -- Museu de Arte Contemporânea de Serralves -- 06.02.2015-20.09.2015 -- Porto